Green and Brown? Globalization and the Environment - James K. Boyce (University of Massachusetts, Department of Economics, 2004)
Globalization - viewed as a process of economic integration that embraces governance as well as markets - could lead to worldwide convergence toward higher or lower environmental quality, or to environmental polarization in which the 'greening' of the global North is accompanied by the 'browning' of the global South. The outcome will not be dictated by an inexorable logic. Rather it will depend on how the opportunities created by globalization alter balances of power within countries and among them.
Keywords: 330; globalization; North-South trade; environment; governance